Religionization of Public Space: Symbolic Struggles and BeyondThe Case of Ex-Yugoslav Societies - Gavrilović, Danijela (Religions, 2018)
The relationship between religious communities and states in the former Yugoslavia is burdened with socialist heritage, but also with conflicts that ensued after the downfall of the socialist regimes. Although the majority of these countries are defined as secular, the struggles have not abated. Following the war conflicts, these struggles moved to the political and symbolic level. The formal and informal influence of religious institutions on the secular state and society continues. Since these countries are formally defined as secular and they strive to join the EU, which supports the separation between church(es) and religious communities and the state, with cooperation based on mutual independence and respect, legal solutions are biased towards acknowledging these principles. Nevertheless, the public sphere has become a battlefield in which public space is being occupied, and a particular way of life and values is imposed. The dynamics of symbolic and other struggles in former Yugoslav countries differ as a consequence of different powers and the relationships between specific religious communities within a state. This paper aims to examine the present religionization of public space that has been taking place, despite the fact that the states in question have been declared as secular (Serbia, Bosnia and Herzegovina, Croatia).